The Bourne ultimatum - Ludlum, Robert (London : Orion Books, 1990)
A mild-mannered professor is forced to asume again the deadly alter ego he created in Vietnam year ago as part of the Medusa Brigade.
Keywords: Adventure fiction; Carlos, the Jackal -- Fiction; Terrorists -- Fiction; United States. Central Intelligence Agency -- Fiction